Scholars, policymakers, and international affairs : finding common cause - Bertucci, Mariano E. , 1975-; Lowenthal, Abraham F. (Johns Hopkins University, 2014)
Clearly written and thoughtfully organized, this innovative book provides analytic insights and practical wisdom for those who want to understand how to build more effective connections between the worlds of thought and action